(untitled) (Palíndromo, 2023)
The present work focuses on the French photographer Jacques-André Boiffard (1902 - 1961) and his first publication in the magazine “Documents” (1929 - 1930), in which he contributed with three photographs of human feet in dialogue with an essay by Georges Bataille, director of the journal. This article aims to carry out a visual reading of these images, relating them to the context of French Surrealism in its emergence, and to modern art and the romantic-symbolist literature produced in France since the 19th century. As this is a photographic production in which fragmented anatomy is highlighted, the discussion presents more recent analyzes of Boiffard’s work, undertaken by art historians and theorists such as Georges Didi-Huberman, Roland Barthes, Briony Fer and Eliane Robert Moraes, in which the relationship between photography and fetishism is discussed, while also exposing how the aggressive visual language chosen by Boiffard, after his approach to Georges Bataille, would represent a rupture with the surrealist imagery, more idealizing, produced by the group’s branch linked to André Breton.